2022
DOI: 10.1021/acs.orglett.2c03364
|View full text |Cite
|
Sign up to set email alerts
|

Decatungstate-Catalyzed Photochemical Synthesis of Enaminones from Vinyl Azides and Aldehydes

Abstract: Visible light-induced synthesis of enaminones from vinyl azides and aldehydes under decatungstate photocatalysis was developed. The reaction proceeds via acyl radical generation from aldehyde, followed by its addition to vinyl azide, nitrogen elimination, hydrogen atom abstraction by the intermediate iminyl radical, and tautomerization. Photochemical synthesis was efficiently conducted under both batch and flow conditions. The method can be applied to various vinyl azides and aldehydes and provides the desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Furthermore, Mitani et al [11] reported that they isolated E-enaminone as an oil, while 5 was a solid with a melting point of 38.5-39.5 °C. On the contrary, the 1 H and 13 C NMR spectra of 5 and the corresponding Z methyl ester reported by Terent ev et al [12] were identical except for the carbinol signals (Table 1).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, Mitani et al [11] reported that they isolated E-enaminone as an oil, while 5 was a solid with a melting point of 38.5-39.5 °C. On the contrary, the 1 H and 13 C NMR spectra of 5 and the corresponding Z methyl ester reported by Terent ev et al [12] were identical except for the carbinol signals (Table 1).…”
Section: Resultsmentioning
confidence: 62%
“…In particular, the resonance of the methyl carbon in 5 was shifted downfield by 7.5 ppm (30.3 vs. 22.8 ppm of 5 compared to E-enaminone), and the alkene carbons resonated at 96.8 and 145.5 ppm for Z-enaminone 5 and at 94.2 and >160 ppm for E-enaminone. Furthermore, Mitani et al [11] reported that they isolated E-enaminone as an oil, while 5 was a solid with a melting point of 38.5-39.5 • C. On the contrary, the 1 H and 13 C NMR spectra of 5 and the corresponding Z methyl ester reported by Terent'ev et al [12] were identical except for the carbinol signals (Table 1). The configurations of E-and Z-enaminones are commonly assigned considering that a strong hydrogen bond between N-H and the carbonyl occurs in Z diastereomers, causing the 1 H-N shift to move to a higher frequency [10].…”
Section: Resultsmentioning
confidence: 91%
“…In the previous investigations on TBADT‐catalyzed additions of benzaldehydes to olefins, the acceptor has been acrylate derivatives, [10b–e,12] 2‐vinylpyridine, [10h] styrene, [10g] phenyl vinyl sulfone, [10j] and acrylonitrile [10a] . The present substrate scope shows that furfural can be added to the same substrates and a number of additional compounds.…”
Section: Resultsmentioning
confidence: 76%
“…Terent'ev and coworkers reported a photocatalytic addition reaction of aldehydes and vinyl azides to give the enaminones, using visible light-induced decatungstate photocatalysis with a 36 W LED lamp (395–400 nm), Scheme 54. 79 This approach enables the effective synthesis of enaminones in both batch and flow conditions. The reaction proceeds through the generation of acyl radicals from aldehyde, which were formed via a hydrogen atom transfer of aldehyde by the photoexcited decatungstate anion (W 10 O 32 4− *).…”
Section: Photochemical Applications Of Tbadt Under Visible Light In V...mentioning
confidence: 99%